2012
DOI: 10.1016/j.bjid.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary cryptococcosis in non-AIDS patients

Abstract: Non-AIDS patients with pulmonary cryptococcosis have a good prognosis with appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…Most of our patients (87.5%) had pulmonary nodules (solitary: 18.8%, multiple: 68.7%). The high frequency of these lesions is consistent with that reported by other studies [8, 11, 12, 14, 15]. The lesions were located predominantly in the lower lung (62.5%) rather than in the middle (18.8%) or upper lung (37.5%), which was also noted in other studies [11, 16–18], and were found mainly in the right (81.3%) rather than the left (50.0%) lung in most patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of our patients (87.5%) had pulmonary nodules (solitary: 18.8%, multiple: 68.7%). The high frequency of these lesions is consistent with that reported by other studies [8, 11, 12, 14, 15]. The lesions were located predominantly in the lower lung (62.5%) rather than in the middle (18.8%) or upper lung (37.5%), which was also noted in other studies [11, 16–18], and were found mainly in the right (81.3%) rather than the left (50.0%) lung in most patients.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical descriptions of pulmonary cryptococcosis in HIV-negative individuals are quite limited because of the rarity of the disease itself. In general, males are more frequently infected than females, and, in the present study, the disease also occurred predominantly in males [11, 12]. Nadrous et al reported that about one-third of immunocompetent patients with pulmonary cryptococcosis were asymptomatic [13].…”
Section: Discussionmentioning
confidence: 48%
“…Usually, the inhalation of Cryptococcus causes focal pneumonitis, and the infection is generally detected as single or multiple pulmonary nodules (11,12). In immunosuppressed patients, focal infection worsens and can cause life-threatening respiratory failure, fungemia, and meningoencephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although latex agglutination can be used as a screening test to detect cryptococcal polysaccharide capsule antigens, this test may yield false positive or negative results. 7,14 Still, Chang et al 3 observed that variations in serum cryptococcal antigen titers were consistent with imaging changes could be used to monitor changes in a patient's condition. Accordingly, extensive development of the latex agglutination test for cryptococcal antigens will significantly influence the detection, diagnosis, monitoring, and treatment of PC.…”
Section: Discussionmentioning
confidence: 99%